Images and Models of Thought - Andrea Casale (Proceedings, 2017)
One really extraordinary ability of the mind is its capacity to match objects and form plausible hypotheses from just a few elements that we see through our eyes. We recognize a feather even if it is mostly covered by a book sitting on top of it. Even if we cannot see the whole shape, we recognize it as pertaining to a category, a set of objects called “feathers”. If by imagination we mean the ability to represent things for ourselves that are not present in the act of sensing, we should realize that the hypothesis of the feather is an imaginative construction of the mind, a mental representation, a model referred to by the sensory input.